Digital Experiments in Learning the Concept of Gravitational Force in Classical Mechanics - Mahombar, Alexander (Lontar Physics Today, 2025)
Gravitational force is one of the fundamental forces that plays an important role in understanding the interaction between massive objects in the universe. However, in physics education, this concept is often difficult to understand concretely due to the limitations of real experiments. This research purpose to analyse the relationship between mass, distance, and gravitational force using the PhET Gravity Force Lab: Basics interactive simulation, as well as to prove its conformity with Newton's Law of Gravity. The research method used was a virtual experiment with a quantitative descriptive approach. Data was obtained by conducting three stages of experiments, namely observing gravitational force on objects of the same and different masses, the relationship between force and mass at a fixed distance, and the relationship between force and distance at a fixed mass. The results showed that gravitational force increased as the mass of objects increased and decreased significantly when the distance between objects increased. The conclusion of this study was that it proved the theory that gravitational force is directly proportional to the product of the masses of the two objects and inversely proportional to the square of the distance between them, in accordance with Newton's Law of Gravity, and showed that the forces were opposite but equal in magnitude, as described in Newton's Third Law.